Proceedings of the First Japan Conference on Graph Theory and Applications, Hakone, Japan, June 1-5, 1986 - Akiyama, J.; Egawa, Y. (Yoshimi), 1953-; Enomoto, Hikoe (Annals of discrete mathematics ;, 1988)
Graph Theory and Applications.